Metabolic Rates Measured in Three Captive Adult Female Walruses (Odobenus rosmarus divergens) While Resting, Swimming, and Diving ... - Karyn D Rode (U.S. Geological Survey, 2021)
This dataset contains measurements of oxygen consumption and carbon dioxide production of 3 adult female walruses (Odobenus rosmarus divergens) while resting, swimming, and diving at the Oceanografic Aquarium in Valencia, Spain. Oxygen consumption and carbon dioxide production was measured for walruses breathing under a respiratory dome while resting at the water surface, under a respiratory dome after swimming and diving, and via breath by breath respirometry using a pneumotachometer when hauled out. ...